IPM for the Philippines - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Farmers throughout the Philippines are learning to use Integrated Pest Management (IPM) rather than pesticides in their efforts to protect their crops from pests. IPM makes use of all available technologies and farming practices in an effort to...